A PRÁTICA DE BANDA NO PROCESSO DE APRENDIZAGEM MUSICAL DOS ALUNOS DE SOPRO E PERCUSSÃO DA ESCOLA DE MÚSICA DO ESTADO DO MARANHÃO. - PEREIRA, Jairo Moraes (2018)
This essay is comprised by a research that has as its object the process of musical learning through band practice. It is noted that this collective practice not only develops the individual musically but also in aspects of sociability. During the research process the perspective is developed individually, socially and artistically through collective dynamics. The insertion of wind and percussion instruments in the Escola de Música do Estado do Maranhão’s (EMEM) programs is approached throughout the essay. Also in the discussion is the set of factors contributing to the pedagogical and artistic activities that EMEM’s students of wind and percussion instruments are involved with. The experience of band practice for musical learning is presented with references to authors and studies in the relevant field. From the collated data, this essay results in the consolidation of the Banda Sinfônica Tomaz de Aquino Leite (BSTAL). An evaluation of the outcomes and the framework of BSTAL in EMEM are also presented.